ASHRAE greenguide the design, construction, and operation of sustainable buildings. (American Society of Heating, Refrigerating and Air-Conditioning Engineers Inc., 2010)
"The third edition of the ASHRAE GreenGuide features information for anyone charged with designing a sustainable building on a variety of green-design issues that should be considered when tasked with this type of project"--Provided by publisher.
Keywords: Sustainable buildings -- Design and construction.; Sustainable architecture.; Buildings -- Environmental engineering.; Sustainable construction.; elektronické knihy; electronic books